Analisis Dampak Alih Fungsi Lahan terhadap Tingkat Ketahanan Pangan Rumah Tangga Petani di Kabupaten Karanganyar Provinsi Jawa Tengah - Yunastiti Purwaningsih; Sutomo Sutomo; Nurul Istiqomah (Universitas Muhammadiyah Yogyakarta, 2015)
The aim of this study were to identify the sources of household income and to analyze factors that influence the accessibility of food of household food rice farmers who are not converted and converted their land. The study was conducted in Karanganyar with sample area was Colomadu District. The analysis technique used was description to identify the sources of household income and two different test mean used to determine whether there are differences in average income from various sources between households who did not convert and those who converted their land function. Logit regression was used to analyze the factors that influence the accessibility of food expenditure. The results on sources of household income showed that most households of both have the main income from farming and self-employed. The monthly average income of farm households who were not converted their land greater than households who converted their land. Land convertion, age, number of household members and assets have significant effect on household food accessibility, while farm income and household income were not significant.